EFFECTIVENESS OF THE MINISTRY OF COMMUNICATION AND INFORMATION IN HANDLING THE MISUSE OF PERSONAL DATA - Riswanih, Ira; Nurwati; Aridhayandi, M. Rendi (DE'RECHTSSTAAT, 2024)
The Ministry of Communication and Information (KOMINFO) has an important role in handling the phenomenon of cybercrime, especially misuse of personal data. The total number of alleged cases of violations of personal data protection from 2019 to May 14, 2024 reached 124 cases. The most violations were data leaks, which were 111 cases. This places Indonesia in the top 10 countries with the most data leaks from January 2020 to January 2024 according to Surfshark, a virtual private network (VPN) company from the Netherlands. Because of this case of personal data leaks, many other institutions have also felt the impact and the impact is not only felt by related institutions but also by the Indonesian people. The Electronic Information and Transactions Law (UU ITE) and the Personal Data Protection Law (UU PDP) were formed because of the urgent need for the people, nation, and state of the Republic of Indonesia today and in the future to be able to compete in the era of globalization. The purpose of this study is to determine how effective the Ministry of Communication and Information is in handling cybercrimes related to misuse of personal data that often occurs in the era of globalization, not only that, this study was also conducted to determine how harmonious the relationship between the Ministry of Communication and Information with other institutions is so that handling misuse of personal data can be carried out more optimally. This study uses a normative legal approach. This study focuses on the analysis of laws and regulations related to the ITE Law and the PDP Law. This type of normative research uses qualitative analysis, namely by analyzing data from library research then processing, generalizing, and analyzing it to answer the problem, then conclusions are drawn regarding the effectiveness of the Ministry of Communication and Information (KOMINFO) in handling cybercrimes related to misuse of personal data. This study shows the findings that there is a fairly severe gap that can be experienced by the Ministry of Communication and Information in carrying out the job description related to personal data protection. This gap does not only come from outside but also from within the Ministry of Communication and Information itself. So if the gap is not immediately closed and fixed, it will have an impact on the programs of the Ministry of Communication and Information, other institutions, and the wider community. The focus of this research will be limited to the many changes that have occurred in the Ministry of Communication and Information itself. This research is relevant to the legal and policy context, especially related to personal data protection. By analyzing this personal data protection policy, it is expected to provide useful input for policy makers, especially for the Ministry of Communication and Information in fixing the gaps that occurred previously so that they do not happen again in the future.